Pengaruh Penjualan Dan Biaya Operasional Terhadap Laba Bersih Pada Perusahaan Percetakan Di Karawang - Indah Puspitasari; Eva Theresna Ruchjana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to study the effect of Sales, Operational Costs on net income. The data in this study were obtained from the Karawang Cipta Grafika financial report. The population of this study is 48 that has been outlier to 46 data with 4 years of research from 2016- 2019 so that the number of samples in this study was 48 samples. The sampling technique used is saturation sampling. The data recovery method is descriptive interaction. Data were analyzed using multiple linear regression. The results of the simultaneous test are (1) Sales, operational costs to net income, (2) partial tests on sales variables have a significant effect on net income, (3) Operational costs increase on net income. Keywords : Net Profit, Sales, Operational Costs